Pengaruh Model Talking Stick Berbantuan Media Video terhadap Aktifitas Bertanya dan Hasil Belajar Kognitif Siswa - Kartini, Lia Maya (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
In the learning process in class students are not given the opportunity to understand the material they are studying, so students lack activity for learning, and have an impact on students' cognitive learning outcomes. The Talking Stick learning model assisted by video media is a solution to increase student activity and student cognitive learning outcomes. This study aims to determine the effect of the Talking Stick learning model assisted by video media on cognitive learning outcomes of students at SMA Negeri 1 Pujut in the 2017/2018 academic year. This research is a quasi-experimental study with a research design using a post-test control group design. The population in this study were all class XI students of SMA Negeri 1 Pujut in the 2017/2018 academic year. The sample of this research is class XI IPA2 as the experimental class and class XI IPA1 as the control class. The determination of the sample was carried out using a non-probability sampling technique. Student asking activity data was obtained using a questionnaire and students' cognitive learning outcomes data were obtained through tests carried out at the end of the learning process. The results of the data analysis showed that the percentage of students' learning motivation was that in the control class a percentage of 77% was obtained and in the experimental class a percentage of 86% was obtained, with a very good category. Data analysis of students' cognitive learning outcomes were analyzed using the t-test. Data on students' cognitive learning outcomes were obtained using SPSS 15 for windows with a sig value of 0.260, because the sig value > α value (0.05), it can be stated that Ha is rejected and H0 is accepted, so it can be concluded that there is no effect of the Talking Stick learning model assisted by video media on cognitive learning outcomes of students at SMA Negeri 1 Pujut in the 2017/2018 academic year.